Increasing imagination creativity students’ of indonesian langauge learning through cloze dilition technique (tcd) in poetry at sixth grade students’ in sd negeri no. 27 sungai tawar kecamatan koto xi tarusan - Eti Eti (Jurnal Ilmiah Pendidikan Scholastic, 2018)
Poetry is a literary material in the elementary school. Because poetry is a literary work that is forgotten spontaneously by using imagination as a guide of the mind, then in the presentation of poetry on the students should use a proper way or technique so that students can imagine as done by the author with a strong imagination to poetry. Through Indonesian Learning to Use Technique Cloze Dilition (TCD) in Poetry To Enhance Creativity Learning Imagination Indonesian Lesson In Grade VI SD Negeri No. 27 Fresh River District of Koto XI Tarusan. Research methods that the authors use to achieve the above objectives is a classroom action research Through Learning Indonesian to Increase creativity imanjination. This study is done in sixth grade students at SD Negeri No. 07 Sungai Tawar Kecamatan Koto XI Tarusan Based on the results of the analysis can be concluded that Through Learning Indonesian language showed improving starting from the results of formative tests. This means that Through Learning Indonesian language managed to improve creativity of students' imangination.